2019
DOI: 10.3390/molecules24213897
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Effect of Different π Bridges Including an Azomethine Group in Triphenylamine-Based Dye for Dye-Sensitized Solar Cells

Abstract: Ten molecules were theoretically calculated and studied through density functional theory with the M06 density functional and the 6-31G(d) basis set. The molecular systems have potential applications as sensitizers for dye-sensitized solar cells. Three molecules were taken from the literature, and seven are proposals inspired in the above, including the azomethine group in the π-bridge expecting a better charge transfer. These molecular structures are composed of triphenylamine (donor part); different combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Recently, two compounds, TP2Py and TP2(3)Bzim, have been found to trigger cell death in response to one or two-photon excitation, which can yield promising results in two-photon photodynamic therapy [ 32 ]. Furthermore, the applications of triphenylamine in quantum dot light-emitting diodes [ 33 ] and dye-sensitized solar cells [ 34 ] should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two compounds, TP2Py and TP2(3)Bzim, have been found to trigger cell death in response to one or two-photon excitation, which can yield promising results in two-photon photodynamic therapy [ 32 ]. Furthermore, the applications of triphenylamine in quantum dot light-emitting diodes [ 33 ] and dye-sensitized solar cells [ 34 ] should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The ƞ values of all the optimized dyes are listed in Table 6 . The dye used for DSSC should exhibit a low value of ƞ to generate better short-circuit current density which results in excellent photoelectric conversion efficiency [ 71 ]. The calculated ƞ values for P1, P2 and P5–P8 ranges from 3.83 to 4.09 eV P1, P5 and P7 have the same HOMO-LUMO gap (1.97 eV) but different values of ƞ.…”
Section: Resultsmentioning
confidence: 99%
“…The electrodonating power (ω − ) has been described as the ability of a molecule to release electron whereas electroaccepting power (ω + ) show the electron acceptor capability of a molecule [ 71 ]. A smaller value of ω − of a system makes it a better donor of electron density while a greater ω + value corresponds to a better capability of accepting electron density.…”
Section: Resultsmentioning
confidence: 99%
“…Xie et al [31,32] investigated the influence of electric field direction on the photovoltaic performance of arylamine organic dye sensitizers. Delgado-Montiel [33] studied the effect of azomethine containing π-bridges on the efficiency of the dye sensitizers. Maurya et al [34] reported using a natural dye extracted from Cassia fistula as a photosensitizer and fabricated a TiO 2 -based DSSC that exhibited η = 0.21.…”
Section: Introductionmentioning
confidence: 99%